The Effect of Emotional Intelligence, Digital Literacy on Innovative Behavior Through Work Ethic As A Mediation Variable in Generation Z Employees - Fitrahtul Aqidah; Muhammad Ridwan Basalamah; M. Cholid Mawardi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The purpose of this study is to analyze the influence of emotional intelligence, digital literacy, and work ethic on innovative behavior in Generation Z employees and to analyze the mediating role of work ethic in the relationship between emotional intelligence and innovative behavior in Generation Z employees. The sample used in this study was 190 active employees in companies or agencies in the Greater Jakarta area aged 15-29 years. The results show that emotional intelligence and digital literacy have a positive influence on the work ethic of Generation Z employees. Furthermore, emotional intelligence, digital literacy, and work ethic have a positive influence on the innovative behavior of Generation Z employees. This study also reveals the mediating role of work ethic in the relationship between emotional intelligence and innovative behavior in Generation Z employees